Influence of the parameters of the layer of ore being brought down on its freezing and losses during the face ore draw - Zubkov Vladimir; Petrov Dmitrii; Bekbergenov Dosanbai (E3S Web of Conferences, 2020)
Application of mining systems with ore caving and adjacent strata, which do not entail high expenditures on delivery of freed ore and rock pressure management, allows to considerably increase efficiency of underground mining of ore deposits in the cryolithic zone. However, their use where permafrost formations are prevalent, requires taking into account factors complicating mining operations, in particular, the congealing of broken ore in the stoping zone. In order to assess the impact of thermal and humidity conditions on the completeness of reserves recovery, a study was carried out to determine the dependence between the volume of losses of broken ore prone to congealing and the width and height of the layer being brought down. Experimental studies were conducted by physical simulation in a cryo chamber on a laboratory bench. The ore drawing was conducted in a uniform sequence at the temperature in the stoping zone of minus 5 ˚C. The final parameter to be determined the loss of ore prone to congealing, was defined as the difference between the mass of ore in the block and the mass of ore drawn. It has been established that the losses of the broken ore due to congealing increase significantly when the depth of the layer being freed decreases and the width increases. The established patterns of influence of parameters of a beaten layer on losses of ore mass will be used during development of recommendations on technology of drawing of ore mass prone to congealing in the negative thermal conditions of underground mines of a cryolithic zone.